Bilateral Pes valgus Deformity in a Shetland Sheepdog - McCarthy, P. E. (Veterinary and Comparative Orthopaedics and Traumatology, 1998)
An eight-month-old, 19.7 kg, male Shetland Sheepdog was diagnosed with a valgus deformity present in both hindlimbs. Anamnesis failed to reveal a traumatic incident to explain the deformities. Bilateral tibial osteotomies and placement of an external skeletal fixation were used in the correction of the defects. Several reports exist concerning angular limb deformities of the rear limb in Shetland Sheepdogs. These facts may represent a breed at risk for such defects.An eight-month-old Shetland Sheepdog with bilateral valgus deformities of the tibiotarsal joint was managed by staged bilateral corrective tibial osteotomies and placement of an external skeletal fixation. Reports of angular limb deformities of Shetland Sheepdogs are reviewed.
Keywords: Angular limb deformity; tibia; external skeletal fixation; pes valgus; Shetland Sheepdog